Analisis Biaya Relevan Untuk Pengambilan Keputusan Jangka Pendek Dalam Pesanan Khusus Pada Ukm Pembuatan Kasur Randu Sari - Yudhanto, Try; Harris, Allan; Uthami, Agnes (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
In the decision-making process, the costs and benefits of one alternative must be compared with the costs and benefits of other alternatives. Special orders are orders outside of regular sales, usually at a price below the regular sales price. One example of an error in decision making by East Lampung Randu Sari Mattress Manufacturing UKM was setting the selling price for a special order because the selling price was lower than the regular selling price. This research uses quantitative and qualitative descriptive research. Quantitative descriptive, ie. describe or describe the application of determining production costs using appropriate cost methods in selecting special order alternative qualitative analysis, namely describing the state of the company, organizational structure, production process and other relevant information. Based on the calculation results, it can be decided that by using the appropriate cost method as a decision making tool, special orders for mattresses, pillows and cushions can be accepted or rejected at UKM Randu Sari UKM East Lampung. Randu Sari Mattress working to obtain optimal profits because the sales proceeds are greater than the production costs. Proper cost accounting will be effective if used by UKM Randu Sari as a decision making tool in East Lampung in accepting or rejecting special orders for mattresses, pillows and pads, because by using the right cost accounting method decision making can run smoothly, managers must can understand which information is important and which is not, and can use relevant data to analyze the various options available and the calculation results prove that UKM Randu Sari in East Lampung can obtain optimal performance using appropriate costs.